2012
DOI: 10.1371/journal.pone.0037655
|View full text |Cite
|
Sign up to set email alerts
|

The Integrative Taxonomic Approach Reveals Host Specific Species in an Encyrtid Parasitoid Species Complex

Abstract: Integrated taxonomy uses evidence from a number of different character types to delimit species and other natural groupings. While this approach has been advocated recently, and should be of particular utility in the case of diminutive insect parasitoids, there are relatively few examples of its application in these taxa. Here, we use an integrated framework to delimit independent lineages in Encyrtus sasakii (Hymenoptera: Chalcidoidea: Encyrtidae), a parasitoid morphospecies previously considered a host gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 70 publications
2
39
0
2
Order By: Relevance
“…Among the encyrtid parasitoids, nine Linnaean species were split into altogether 32 DNA‐based entities, including one species that was split into six new entities. These findings are in line with other studies, including a threefold increase in the number of genetically delimited Psyllaephagus parasitoids over recognized morphospecies (Hall et al., ) and the detection of three cryptic species in Encyrtus sasakii based on DNA barcoding, geometric morphometrics, and mating tests (Chesters et al., ). These cryptic species generally attack a single‐host species, which might suggest that most generalists of encyrtids are complexes of cryptic species with limited host ranges.…”
Section: Discussionsupporting
confidence: 91%
“…Among the encyrtid parasitoids, nine Linnaean species were split into altogether 32 DNA‐based entities, including one species that was split into six new entities. These findings are in line with other studies, including a threefold increase in the number of genetically delimited Psyllaephagus parasitoids over recognized morphospecies (Hall et al., ) and the detection of three cryptic species in Encyrtus sasakii based on DNA barcoding, geometric morphometrics, and mating tests (Chesters et al., ). These cryptic species generally attack a single‐host species, which might suggest that most generalists of encyrtids are complexes of cryptic species with limited host ranges.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, resolving species complexes gives a unique opportunity to more precisely define or even deeply revise ecological interactions (see, for instance, the following recent publications for case study involving arthropods: Chesters et al , ; Knee et al , ; Muirhead et al , ; Miller et al , ). In our study, almost all of the most common species ( E. confusus , E. kiefferi , E. gemellus and E. urozonus ) were confirmed to be generalist species with likely wide host ranges because they were recovered from at least two insect orders (Diptera and Hymenoptera) and in association with various plants (see Appendix S1 and Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reactions (PCR) were performed following Chesters et al . (). The COI gene was amplified using universal primers LCO1490 and HCO2198 (Folmer et al ., ), and the PCR cycle program for COI followed Hebert et al .…”
Section: Methodsmentioning
confidence: 97%
“…In the past decade, DNA barcoding has been widely used in identification of Hymenoptera parasitoids (Derocles et al ., ; Smith et al ., ; Novković et al ., ; Babcock & Heraty, ; Ratcliffe et al ., ; Jinbo et al ., ; Zhang et al ., ; Chester et al ., ; Emam et al ., ). Recent studies of soybean aphid parasitoids (Wyckhuys & Heimpel, ; Wyckhuys et al ., ; Starý et al ., ; Wu et al ., ; Desneux et al ., ; Petrović et al ., ) indicated that DNA barcoding may be a useful tool for their identification.…”
Section: Introductionmentioning
confidence: 97%